The Influence Country of Origin on Purchase Intention Korean Food with Moderating Consumer Ethnocentrism on Generation Z in East Java - Erica Adriana; Ivana Devianti Afrizal; Anna Triwijayati (Indonesian Journal of Business Analytics, 2023)
The growing food industry in Indonesia is characterized by many Generation Z who are interested in trying various foods from abroad, this development has targeted many Generation Z as their customers. It is important for business people to understand how Generation Z views the country of origin of product producers and their ethnocentrism. The purpose of this study is to determine the effect of country of origin on Korean food purchase intention with moderation of consumer ethnocentrism in East Java.This research uses Quantitative methods with the MRA (Moderated Regression Analysis) model, the respondents are Generation Z in East Java aged 17-26 years with a total of 272 samples, the research data source uses a questionnaire. Based on the results of the study, it was found that consumer ethnocentrism moderates country of origin on purchase intention positively and significantly.